Major element chemistr yof fallout tephra from ODP Hole 125-782A - Susanne M Straub (PANGAEA, 2003)
New and published analyses of major element oxides (SiO2, TiO2, Al2O3, FeO*, MnO, MgO, CaO, K2O, Na2O and P2O5) from the central Izu Bonin and Mariana arcs (IBM) were compiled in order to investigate the evolution of the IBM in terms of major elements since arc inception at ~49 million years ago. The database comprises ?3500 volcanic glasses of distal tephra fallout and ?500 lava samples, ranging from the Quaternary to mid-Eocene in age. The data were corrected to 4 wt% MgO in order to display the highly resolved temporal trends. These trends show that the IBM major elements have always been “arc-like” and clearly distinct from N-MORB. Significant temporal variations of some major element oxides are apparent. The largest variations are displayed by K4.0. The data support a model wherein the K2O variability is caused by the addition of slab component with strongly differing K2O contents to a fairly depleted subarc mantle; variable extents of melting, or mantle heterogeneity, appear to play a negligible role. The other major element oxides are controlled by the composition and processes of the subarc mantle wedge. The transition from the boninitic and tholeiitic magmatism of the Eocene and Oligocene to the exclusively tholeiitic magmatism of the Neogene IBM is proposed to reflect a change in the composition of the subarc mantle wedge. The early boninitic magmas originate from an ultra-depleted subarc mantle, that is residual to either the melting of E-MORB mantle, or of subcontinental lithospheric mantle. During the Eocene and Oligocene, this residual mantle is gradually replaced by Indian MORB mantle advected from the backarc regions. The Indian MORB mantle is more radiogenic in Nd isotope ratios but also more fertile with respect to major and trace elements. Therefore the Neogene tholeiites have higher Al2O3 and TiO2 contents and lower mg# numbers at given SiO2 content. After the subarc mantle replacement was complete in the late Oligocene or early Miocene, the Neogene IBM entered a “steady state” that is characterized by the continuous advection of Indian MORB mantle from the reararc, which is fluxed by fluids and melt components from slab. The thickness of the IBM crust must have grown with time, but any effects of crustal thickening on the major element chemistry of the IBM magmas appear to be minor relative to the compositional changes that are related to source composition. Therefore next to the processes of melting, the composition of the mantle sources must play a major role in creating substantiative heterogeneities in the major element chemistry of the arc crust.
Supplement to: Straub, SM (2003): The evolution of the Izu Bonin - Mariana volcanic arcs (NW Pacific) in terms of major element chemistry. Geochemistry, Geophysics, Geosystems, 4(2), 1018, https://doi.org/10.1029/2002GC000357